PENGARUH LATIHAN SQUARE RUN TERHADAP KELINCAHAN PADA TIM PUTRA SMA OAHRAGA PEKANBARU - Selpitri, Desi; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: According to the problem in the male volleyball team of SMA OLAHRAGA PEKANBARU, the researcher observed the training or the match time that the male volleyball team had a lot of deficiencies. One of them was the agility to recieve the smash or block. As a result, the players could not manage the smash, block, or service. The aim of the research was to obtain the effect of Square Run training towards the agility of the male volleyball team of SMA OLAHRAGA Pekanbaru. The population of the research was the players of the male volleyball team followed the training of volleyball at SMA OLAHRAGA Pekanbaru in the amount of 12. The technic of obtaining the samples was Total Sampling. The data analysis used T-Test. Based on the the analysis, it was able to be concluded that there was a significant effect between Square Run training and the agility of the players in the male volleyball team of SMA OLAHRAGA Pekanbaru with the result tcount 3.850 > ttable 1,796 to α = 0.05. It proved that by using Square Run training increased the better agility.Key Words: Square Run training, Agility